Detection of spermatogonial stem cells in testicular tissue of dogs with chronic asymptomatic orchitis - Reifarth, Larena; Körber, Hanna; Packeiser, Eva-Maria; Goericke-Pesch, Sandra (Frontiers in Veterinary Science, 2023)
Chronic asymptomatic idiopathic orchitis (CAO) is an important, but neglected cause of acquired infertility due to non-obstructive azoospermia (NOA) in the male dog. The similarity of the pathophysiology in infertile dogs and men supports the dog’s suitability as a possible animal model for studying human diseases causing disruption of spermatogenesis and evaluating the role of spermatogonial stem cells (SSCs) as a new therapeutic approach to restore or recover fertility in cases of CAO. To investigate the survival of resilient stem cells, the expression of protein gene product (PGP9.5), deleted in azoospermia like (DAZL), foxo transcription factor 1 (FOXO1) and the tyrosine-kinase receptor (C-Kit) were evaluated in healthy, and CAO affected canine testes. Our data confirmed the presence of all investigated germ cell markers at mRNA and protein level. Besides, we postulate a specific expression pattern of FOXO1 and C-Kit in undifferentiated and differentiating spermatogonia, respectively, whereas DAZL and PGP9.5 expression were confirmed in the entire spermatogonial population. Further, this is the first study revealing a significant reduction of PGP9.5, DAZL and FOXO1 in CAO at protein and/or gene expression level indicating a severe disruption of spermatogenesis. This means that chronic asymptomatic inflammatory changes in CAO testis are accompanied with a significant loss of SSCs. Notwithstanding, our data confirm the survival of putative stem cells with the potential of self-renewal and differentiation and lay groundwork for further research into stem cell-based therapeutic options to reinitialize spermatogenesis in canine CAO affected patients.